Emotions and Irony in Usman Awang's Poems: A Pragmatic Interpretation: (Emosi dan Ironi dalam Puisi Usman Awang: Tafsiran Pragmatik) (Jurnal Bahasa, 2018)
This study examines emotions from the perspective of language and linguistics that is usually examined in the field of psychology. Relevance Theory (RT ) which was developed by Sperber and Wilson (1986) served as the analytical framework. Data were drawn from the works of Usman Awang, the National Laureate of Malaysia. Four poems were selected and analyzed to detect the element of irony which is also known as the language of satire. Both qualitative and quantitative methods were used. The data were analyzed using the concepts as stipulated in Relevance Theory. After accessing the meaning, the questionnaire was distributed to 50 respondents in order to identify the implicit elements of emotion. Findings reveal that implicit emotions were embodied within the irony which could be felt by readers after uncovering the implicit meaning of the poems using Relevance Theory. Thus, this study proved that although the theory used was a linguistic one specifically drawn from the field of pragmatics, however, the study has succeeded in unlocking the meaning and implicit emotions in the poems. As such, it is found that the field of psychology can be combined with the field of language and linguistics in order to study the aspect of emotions.Keywords: emotion, irony, language and linguistics, pragmatics, relevance theory